CPR Knowledge: The Key to ICU Nurses’ Readiness in Facing Emergency Conditions - Angriawan Angriawan; Ilyas I Made Permata Gusti; Muhammad Reza Fahlevi Hanafi; Nadya Ulfa Kesumawardani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Cardiovascular disease remains the leading cause of death worldwide, and sudden cardiac arrest is a life-threatening emergency that requires immediate management through Cardiopulmonary Resuscitation (CPR). The low survival rate of patients is often attributed to insufficient knowledge and preparedness among healthcare professionals in performing CPR. This study aimed to analyze the correlation between nurses’ level of knowledge and their readiness to perform CPR in the ICU of Grandmed Hospital, Lubuk Pakam. A quantitative method with a cross-sectional and correlational design was employed. The study population included all 19 ICU nurses, selected using a total sampling technique. Data were collected using a structured questionnaire covering respondent characteristics, CPR knowledge based on American Heart Association (AHA) standards, and readiness to respond to emergency situations. Univariate analysis revealed that the majority of respondents were female (68.4%), aged 20–29 years (68.4%), held a professional nursing degree (63.2%), had 1–5 years of work experience (63.2%), and more than half had never attended CPR training (52.6%). Furthermore, 84.2% of nurses demonstrated good knowledge, and 78.9% were categorized as highly ready. The Spearman’s rho test indicated a strong and significant positive correlation between knowledge and readiness (r = 0.629; p = 0.004). In conclusion, the higher the nurses’ level of knowledge regarding CPR, the better their readiness to handle sudden cardiac arrest in the ICU.